The Ameliorative Effects of Caffeic Acid Phenethyl Ester in Cisplatin-Induced Nephrotoxicity: Assessment of the Oxidative Stress an Inflammation - Ceylan,Tayfun (Sociedad Chilena de Anatomía, 2021)
SUMMARY: The aim of this study is to determine the potential therapeutic effects of CAPE in CP-induced nephrotoxicity in rats. Cisplatin (CP) is an antineoplastic chemotherapeutic used for treatment of many cancer types but its applications may induce nephrotoxicity. Caffeic acid phenethyl ester (CAPE) is an active component of propolis and it has several important physiological activities. Rats were divided into four groups: Control, CAPE (10 µmol/kg/i.p), CP (7 mg/kg/i.p), and CP+CAPE (7 mg/kg/i.p, CP and 10 µmol/kg/i.p, CAPE). After administrations, animals were sacrificed, and kidney tissues were extracted. Histopathological changes were evaluated and TNF-α and IL-6 immunostaining were performed. Moreover, tissue SOD, CAT and MDA levels were measured by ELISA assay to assessment of oxidative stress and lipid peroxidation. CP group showed histopathological deterioration compared to the Control group and CAPE treatment attenuated this damage. When compared with Control and CAPE group, an increase in TNF-α and IL-6 immunoreactivities and tissue MDA levels were observed in the CP group while a decrease in tissue SOD and CAT levels were detected. Furthermore, an improvement was observed in the CP+CAPE compared to the CP group. We suggest that CAPE can be used as a therapeutic agent to attenuate the toxic effects of cisplatin, thanks to its antioxidant and anti-inflammatory properties.